Improving renewable energy resource assessments by quantifying landscape beauty - Russell McKenna; Jann Michael Weinand; Ismir Mulalic; Stefan Petrovic; Kai Mainzer; Tobias Preis; Helen Susannah Moat (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2020)
A cost-efficient and sustainable energy transition requires reliable information about the distribution of renewable energy resources. Here we draw on over 1.5 million scenicness ratings of around 200,000 geotagged photographs from Scenic-Or-Not to quantify the aesthetic value of the landscapes in which onshore wind energy installations could be situated in Great Britain. An analysis of planning applications provides quantitative evidence that onshore wind projects are more likely to be rejected when proposed in more scenic areas. Exploiting further open data sources including OpenStreetMap, we build on these findings to generate new estimates of the feasible potential and costs for onshore wind in Great Britain, which we find to be around 1700 TWh and 280 billion respectively. We also uncover a strong spatial correlation between scenicness and the quality of the wind resource, implying inevitable trade-offs between cost-efficiency and public acceptance.
Keywords: 330